2008
DOI: 10.1111/j.1468-0475.2008.00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Expectation Formation Involving Several Sources of Information

Abstract: Experimental studies of expectation formation of subjects are predominantly limited to the prediction of one single time series despite the practical relevance of expectations in situations with multiple sources of information. In this paper, we report on an experiment in which subjects are given time series (indicators) as additional information for the judgemental forecast of a stationary time series. The quality and the number of these indicators are varied in three versions of a forecasting experiment. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…1 shows all time series applied in the experiment. Becker and Leopold-Wildburger (2000) and Becker et al (2004) reported on four versions (versions 0-3) of the experiment, in which no, one or two indicators were available to the subjects. The study at hand mainly deals with the versions 4-6 in which up to two strong and two weak indicators are presented to the participants for their forecast of x t .…”
Section: The Experimental Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…1 shows all time series applied in the experiment. Becker and Leopold-Wildburger (2000) and Becker et al (2004) reported on four versions (versions 0-3) of the experiment, in which no, one or two indicators were available to the subjects. The study at hand mainly deals with the versions 4-6 in which up to two strong and two weak indicators are presented to the participants for their forecast of x t .…”
Section: The Experimental Contextmentioning
confidence: 99%
“…All indicators have a constant lead of one period and they are available to the subjects when they make a forecast for the next period. Results of four prior versions of this experiment are available (see Becker and Leopold-Wildburger, 2000;Becker et al, 2004): In version 0 no indicator is presented, in version 1 (2) one strong (weak) indicator is available and in version 3 both indicators are provided.…”
Section: Introductionmentioning
confidence: 99%
“…In the early 1960's Becker conducted a prediction experiment using this time series without a break over 42 periods. Recently Becker et al (2007Becker et al ( , 2008 presented a simple heuristic based on Becker's (1967) forecasting program for the modeling of average forecasts of the subjects for the same class of time series. The authors showed that the model forecasts the behavior of the subjects better than the Rational Expectations Hypothesis (REH) when indicators are in the information set of the participants.…”
Section: Introductionmentioning
confidence: 99%
“…These settings (see e.g. Becker et al, 2008) primarily focus on showing subjects' inability to rationally process graphical or statistical information, which is interpreted as a refutation of the rational expectation hypothesis. Secondly, we implement a coordination mechanism as an alternative mode of generating payoffs.…”
Section: Introductionmentioning
confidence: 99%